Implementasi Program Adiwiyata dalam Menumbuhkan Sikap Peduli Lingkungan di SD Negeri Sugihan 02 - Karina Mulyawati; Yessi Andrayani; Arya Musthofa; Mutiara Dana Elita; Sagitawati Putu P (Yayasan Al-Afif, 2025)
This study aims to examine the implementation of the Adiwiyata program in fostering environmental awareness, identify the obstacles faced by the school, and describe the efforts made to overcome these challenges at SD Negeri Sugihan 02. The research employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. The findings indicate that the Adiwiyata program has been implemented effectively through school policies, an environment-based curriculum, participatory activities, and the management of environmentally friendly facilities. The challenges identified include limited student awareness, insufficient facilities, and the suboptimal involvement of parents. The school has made various efforts to address these issues, such as establishing routines, conducting socialization activities, strengthening school culture, and collaborating with the school committee and the community. Overall, the Adiwiyata program has proven to contribute significantly to shaping students’ environmental awareness